Note on the Tableau Technique for Commutative Transition Systems - Srba, Jirí (BRICS Report Series, 2001)
We define a class of transition systems called effective commutative transition systems (ECTS) and show, by generalising a tableau-based proof for BPP, that bisimilarity between any two states of such a transition system is decidable. It gives a general technique for extending decidability borders of strong bisimilarity for a wide class of infinite-state transition systems. This is demonstrated for several process formalisms, namely BPP process algebra, lossy BPP processes, BPP systems with interrupt and timed-arc BPP nets.